The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
PeerJ Inorganic Chemistry 2021
DOI: 10.7717/peerj-ichem.2
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction and theoretical study of the transition 2H-3R polytypes in Nb1+xSe2 (0 < x < 0.1)

Abstract: Single crystals of 2H and 3R niobium diselenide were grown by a chemical transport reaction. The current determinations by single crystals X-ray diffraction reveal a non-stoichiometric composition. The structures are built from Se—Nb—Se slabs with Nb in trigonal prismatic coordination whereas the extra or additional Nb atoms are located in the octahedral holes between the slabs giving rise to the formula 2H and 3R-Nb1+xSe2 with 0.07 < x < 0.118. In particular, vacancy and Nb-Nb interactions may play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Our STEM images disclose that epitaxial films of Nb 1+x Se 2 near a global x ~0.29 exhibit a nanoscale separation into 180°-stacked layers with a large number of Nb intercalants, perhaps several tens of percentage occupancy (considering the average x value), and 0°-stacked layers whose number of Nb intercalants falls close to the detection limit. Bulk studies have shown that the polytype of pristine NbSe 2 is 2H a with 180°s tacking, and that a few percent of excess Nb should stabilize the 3R polytype with 0°stacking [24][25][26][27] . Here, the situation seems to be reversed, with the 180°-stacked layers hosting a much greater number of Nb intercalants than the 0°-stacked layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our STEM images disclose that epitaxial films of Nb 1+x Se 2 near a global x ~0.29 exhibit a nanoscale separation into 180°-stacked layers with a large number of Nb intercalants, perhaps several tens of percentage occupancy (considering the average x value), and 0°-stacked layers whose number of Nb intercalants falls close to the detection limit. Bulk studies have shown that the polytype of pristine NbSe 2 is 2H a with 180°s tacking, and that a few percent of excess Nb should stabilize the 3R polytype with 0°stacking [24][25][26][27] . Here, the situation seems to be reversed, with the 180°-stacked layers hosting a much greater number of Nb intercalants than the 0°-stacked layers.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that TMDCs, especially with group-5 metal atoms, i.e., M = V, Nb, or Ta, undergo complex transformations of stacking polytypes upon excess M stoichiometry 23,24 . For example, bulk samples of Nb 1+x S 2 and Nb 1+x Se 2 undergo a transition from a 2H a polytype with 180°stacking of layers to a 3R polytype with 0°stacking when x crosses a threshold around 0.03-0.07, presumably because the 3R polytype better accommodates the increasing number of Nb intercalants in its interstitial voids [24][25][26][27] . With larger values of x, polycrystalline samples with 2H a , 2H b , and 3R polytypes and Nb intercalants have been stabilized 24 , but less is known about this regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation